Born to be killed - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Smoke Jensen novel of the West, 2026)
Smoke Jensen travels with a wagon train of Civil War widows and orphans on a journey to Wyoming, where they hope to establish new lives.